DEFINITION OF NUTRITIONAL REQUIREMENTS FOR ZINC IN BROILERS USING BAYESIAN METHODOLOGY - MANGUEIRA, Rick Anderson Freire; SAVIAN, Taciana Villela; LEANDRO, Roseli Aparecida (Brazilian Journal of Biometrics, 2022)
Studies about nutritional requirements of animals are important, among other reasons, in order to have an adequate knowledge of the essential levels of minerals added in feed, and thus, to produce it efficiently, to avoid elimination of minerals through feces and urine and prevent intoxication of the animal due to excess of a certain nutrient. The data used for the study are related to Zinc (Zn) content, in ppm, in the broilers’ tibia that received the same feed with nine different dosages of zinc. The quadratic segmented regression model with response plateau and the nonlinear segmented regression model with response plateau were fitted to data, using a bayesian approach and considering cases of homogeneity and heterogeneity of variances. The fitted models considering heterogeneity of variances were more appropriate for the data, according to the DIC fit criterion.